Pelatihan Media Pembelajaran berbasis IT bagi Tutor PKBM di Kota Palangkaraya - Rahmatullah; Fathul Zannah (Aisha Edutama, 2024)
The rapid development of technology requires improvements in its implementation in learning activities, one of which is to use it as a learning medium. This activity aims to provide training in the use of information technology-based learning media in the form of plickers, one of which is to tutors at PKBM in Palangkaraya City, namely PKBM Luthfillah and PKBM Cahaya Bangsa. The training activity used lecture methods and direct practice which was carried out at the Matan Andau Resort on February 10 2024. This learning media training in the form of plickers is expected to be able to equip the tutors at PKBM to increase competency in helping to improve the quality of education.